The Availability Of Essential Parkinson's Disease Medications In The Public And Private Sectors And The Suitability Of Storage Conditions For Medications In Nafusa Mountain, Libya (Comprehensive Journal of Science, 2025)
In the recent years, parkinson’s disease has been distributed widely over the worldspecifically among elderly people. The major aim of this research is find out the availabilityrates for the essential parkinson’s disease medications (PDMs) as well as studying thesuitability of storage conditions of medications in the major cities of Nafusa Mountain,Libya. A survey was completed after a field visit to the major hospitals and to the biggestprivate pharmacies in the area of study. The results showed that the essential PDMs were notavailable in the public sector. In the private sector, the highest availability rate were 66.66%in Gharyan pharmacy. The availability rates of biperiden and levodopa/carbidopa were 10%and 20% respectively in the private sector. Regarding the suitability of storage conditions ofmedicines in the dispensing area, the storage conditions were 100% compliance in AlAwainiya hospital (public sector), Jadu hospital (public sector), Jadu pharmacy (privatesector) and Al-Zintan pharmacy (private sector). It is recommended to address the root causesof the low availability of essential PDMs in both sectors. In additions, try to improve thestorage conditions for medicines in the dispensing areas.
Keywords: : Parkinson’s disease, essential medications, biperiden, levodopa/carbidopa